Prevalence of mitochondrial gene mutations among hearing impaired patients. Issue 1 (1st January 2000) - Usami, Shin-ichi; Abe, Satoko; Akita, Jiro; Namba, Atsushi; Shinkawa, Hideichi; Ishii, Masanori; Iwasaki, Satoshi; Hoshino, Tomoyuki; Ito, Juichi; Doi, Katsumi; Kubo, Takeshi; Nakagawa, Takashi; et al.
Abstract : The frequency of three mitochondrial point mutations, 1555A→G, 3243A→G, and 7445A→G, known to be associated with hearing impairment, was examined using restriction fragment length polymorphism (RFLP) analysis in two Japanese groups: (1) 319 unrelated SNHL outpatients (including 21 with aminoglycoside antibiotic injection history), and (2) 140 cochlear implantation patients (including 22 with aminoglycoside induced hearing loss). Approximately 3% of the outpatients and 10% of the cochlear implantation patients had the 1555A→G mutation. The frequency was higher in the patients with a history of aminoglycoside injection (outpatient group 33%, cochlear implantation group 59%). One outpatient (0.314%) had the 3243A→G mutation, but no outpatients had the 7445A→G mutation and neither were found in the cochlear implantation group. The significance of the 1555A→G mutation, the most prevalent mitochondrial mutation found in this study of a hearing impaired population in Japan, among subjects with specific backgrounds, such as aminoglycoside induced hearing loss, is evident.